Bench press training program with attached chains for female volleyball and basketball athletes - Burnham, T. R.; Ruud, J. D.; McGowan, R. (Perceptual and Motor Skills, 2010)
Attaching chains to barbells to increase strength and power has become popular for athletes; however, little scientific evidence supports this practice. The present purpose was to compare chain training to traditional training for the bench press. Women collegiate athletes in volleyball and basketball (N = 19) participated in a 16-session bench press program. They were matched into either a Traditional or a Chain training group by 1-repetition maximum (1RM). The Traditional group performed the bench press with conventional equipment, while the Chain group trained with attached chains (5% of weight). Analysis showed a significant increase in 1RM for both groups over 16 sessions, Traditional +11.8% and Chain +17.4%. The difference between the groups was not statistically significant, but suggests the women who trained with attached chains improved their bench press more than the Traditional group.